Psychological inflexibility and suicide risk in adolescents from Cerro de Pasco, Peru - Salcedo-Ramón, Henry (2024)
Objective. To identify the effect of psychological inflexibility on suicide risk among adolescents from a public educational institution in Cerro de Pasco, Peru. Methods. The study was explanatory, cross-sectional, and included observable variables. The sample, selected through non-probabilistic intentional sampling, consisted of 193 high school students from an institution in Cerro de Pasco. The students were assessed using the Avoidance and Fusion Questionnaire for Youth (AFQ-Y) and the Suicide Risk Scale (SRS). Results. The findings show that psychological inflexibility has a direct effect on suicide risk (B = .516, r 2 = .262, p < .001; f 2 = .355). Additionally, psychological inflexibility was found to exert a direct effect on depression and hopelessness(B = .397; r 2 = .153; p < .001; f 2 = .181), suicidal  deation and intent (B = .447; r 2 = .196; p < .001; f 2 = .244), social isolation (B = .509; r 2 = .255; p < .001; f 2 = .342), and lack of family support (B = .457; r 2 = .205; p < .001; f 2 = .258). Conclusions. Indicators of psychological inflexibility influence the confguration of suicide risk by increasing depression and hopelessness, suicidal ideation and intent, social isolation, and lack of family support among adolescents in a school in Cerro de Pasco.